2015
DOI: 10.1186/s12889-015-1569-9
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and eating behaviors in school children and adolescents –data from a cross sectional study from Bucharest, Romania

Abstract: BackgroundEpidemiological data on obesity prevalence are scarce in Romanian population. Consequently, the aim of our study was to evaluate the prevalence of obesity and unhealthy behaviors among school children and adolescents from Bucharest, Romania.MethodsCross-sectional study, 866 participants (53.2% girls, 46.8% boys, age range 6–18 years), selected by systematic sampling with probability-proportionate-to-size from all Bucharest’s schools.Measurements: height, weight and a questionnaire to collect informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 26 publications
(38 reference statements)
5
31
0
6
Order By: Relevance
“…This decline may be due partly to the attenuation of the positive energy, balanced during puberty or a possible positive trend of increased weight across generations due to exposure to environmental factors earlier in life. In agreement with previous studies [17], we observed a greater prevalence of obesity in male children and adolescents than in female children and adolescents. Gender-specific differences may be explained by the greater lean mass associated with a muscular male body build and bone mass.…”
Section: Discussionsupporting
confidence: 93%
“…This decline may be due partly to the attenuation of the positive energy, balanced during puberty or a possible positive trend of increased weight across generations due to exposure to environmental factors earlier in life. In agreement with previous studies [17], we observed a greater prevalence of obesity in male children and adolescents than in female children and adolescents. Gender-specific differences may be explained by the greater lean mass associated with a muscular male body build and bone mass.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, there was a substantially greater tendency for participants to read labels before food purchases following an intervention in another study [27]. Collectively, these results demonstrate the importance of customized educational programs to promote healthy lifestyles [28]. …”
Section: Discussionmentioning
confidence: 95%
“…Body mass index is calculated as the ratio of weight in kilograms to height in square meters. According to the US Center for Disease Control and Prevention (CDC, 2000), BMI less than 85th is defined as underweight for one's age and gender, between the 85th and 95th percentile as overweight and above 95th as obese (20)(21)(22). Systolic and diastolic blood pressure was measured from the right arm twice at least 5 minutes after rest (during this period, the student's hands were in a suspended state) using a Japanese calibrated aneroid sphygmomanometer with an appropriate cuff size and a Japanese stethoscope.…”
Section: Methodsmentioning
confidence: 99%